EFFICIENT MUTUAL FUND MARKETS a global perspective. (ROUTLEDGE, 2026)
This book covers a new and innovative approach to the issue of investment portfolio efficiency from the perspective of a large institutional investor. It discusses the challenges relating to changes in returns on the international stock market, with particular emphasis on investments.Instead of focusing on just one designated market, the book examines four diversified, developed markets, and models the Polish market as a representative of emerging markets. The authors argue that the current market for available financial instruments, mainly derivatives, may be an example of a partially complete market. With such assumptions, they test selected markets, assuming that a representative investor, such as an investment fund, makes rational decisions and uses all available financial instruments. The research conducted in the book is unique in its assumption that investors form portfolios that consider the structure of the company's financial results. The significant impact that the financial crisis in the United States since 2007, the COVID-19 pandemic, and Russia's aggression against Ukraine have had on investors' decisions is also discussed.The book will find an audience among researchers, scholars, and students specialising in finance and capital market investments.